Reframing Spatial Hazard Education with Interactive Digital Media and Regionalized Content in Secondary Schools - Faridh Arganatha Diwangkara; Purwanto; ivy, Tan Geok Chin (CV Bumi Spasial, 2025)
Modern geography education necessitates technology-integrated materials to visualize complex spatial phenomena effectively. Addressing this need, this study employs the ADDIE model to develop